2021
DOI: 10.3389/frwa.2020.620704
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Ecological Health of Afrotropical Rivers Using Fish Assemblages: A Case Study of Selected Rivers in the Lake Victoria Basin, Kenya

Abstract: Streams and rivers are globally threatened ecosystems because of increasing levels of exploitation, habitat degradation and other anthropogenic pressures. In the Lake Victoria Basin (LVB) in East Africa, these threats are mostly caused by unsustainable land use; however, the monitoring of ecological integrity of river systems has been hampered by a lack of locally developed indices. This study assessed the health of four rivers (Nzoia, Nyando, Sondu–Miriu and Mara) on the Kenyan side of the LVB using physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
2
11
0
Order By: Relevance
“…On the other hand, the shorter period of breeding happening from October to December is due to shorter rains occurring later every year (Kizza et al, 2009). Whereas breeding for this species follows specific pattern, there are chances that this is affected by anthropogenic activities on the river catchments such as direct disposal of organic and inorganic wastes particularly from agriculture and other development activities (Achieng et al, 2021;Aura et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the shorter period of breeding happening from October to December is due to shorter rains occurring later every year (Kizza et al, 2009). Whereas breeding for this species follows specific pattern, there are chances that this is affected by anthropogenic activities on the river catchments such as direct disposal of organic and inorganic wastes particularly from agriculture and other development activities (Achieng et al, 2021;Aura et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is among fish species that can sustain commercial riverine fishery in the basin (Masese et al, 2020). In Kenya it's found in rivers Nzoia, Nyando, Yala, Sondu, Kuja-Migori and Mara among others (Achieng et al, 2021;Chemoiwa et al, 2017). Although, L. altianalis is considered a species of less concern, the indigenous stocks face a serious threat due to degradation of their habitats (Ondhoro et al, 2017;Chemoiwa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of this huge body of literature offers opportunities to strengthen the use of BCG, especially overcoming problems of determining undisturbed ecological conditions as well as the knowledge needed during pre-and post-status of ecosystems during rehabilitation programs. Only a few studies exist on fish bioassessment (Raburu and Masese, 2012;Achieng et al, 2021), and we recommend their continued promotion because they are sensitive to effects of poor agricultural practices and deforestation, which cause sedimentation and loss of habitat diversity and heterogeneity (Hocutt et al, 1994;Ganasan and Hughes, 1998;Toham and Teugels, 1999). Similarly, the use of diatoms in bioassessment of rivers is still at a nascent stage in Kenya (Ndiritu et al, 2006;Triest et al, 2012); however, findings of this study found them to be very reliable in assessing river conditions, especially the effects of climate on water quality.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid urban expansion and industrial developments worldwide, as well as intensive farming, have contributed to the deterioration of chemical water quality and alterations of physical habitats in rivers and streams [ 6 , 7 ]. Such modifications influence the aquatic biota composition and trophic interactions throughout the food chain, thereby damaging the overall river health and shifting the community structures of low- to high-level trophic biota [ 8 , 9 ]. Concomitant modifications are more intricate in riverine ecosystems, particularly in Asian temperate river systems that are primarily regulated by the seasonal monsoon [ 10 ].…”
Section: Introductionmentioning
confidence: 99%